ANALYSIS OF THE RELATIONSHIP BETWEEN NUTRITIONAL INDICATORS AND HDI IN KARANGANYAR REGENCY - elisa danik kurniawati (STIKes Kepanjen, 2022)
Introduction: Health as the foundation of human life to improve the quality of human resources can be seen from the development of nutrition. Aim. This study aims to determine the relationship and predict the influence of nutrition indicators on HDI in Karanganyar Regency in 2017-2021. Method: Secondary data related to nutrition indicators was taken from the Karanganyar District Health Office for 2017-2021 while HDI data was taken from the official website of the BPS Central Java Province for 2017-2021. The bivariate analysis was analyzed using a correlation test while the multivariate analysis used multiple linear regression tests. Results: The multivariate analysis show that for HDI the variable that has an effect is the percentage of stunting with the regression model Y = 76.140 – 0.041*X4. While the bivariate results show that variable X1 has a moderate strength of relationship with variable Y (r=0.574), variable X2 has a strong relationship with variable Y (r=-0.798), variable X3 has a strong relationship with variable Y (r=0.620), variable X4 has a very strong relationship with variable Y (r=-0.995), and variable X5 has a very strong relationship with variable Y (r=-0.973). Conclusion: It was concluded that based on bivariate analysis, the percentage of stunting and wasting had an effect on HDI. However, in multivariate analysis it is known that only the stunting variable is able to predict the HDI score each year.